Playing with the good guys: A public good game with endogenous group formation - Kjell Arne Brekke; Karen Evelyn Hauge; Jo Thori Lind; Karine Nyborg (University of Oslo, Department of Economics, 2009)
In public good games, voluntary contributions tend to start of high and decline as the game is repeated. If high contributors are matched, however, contributions tend to stay high. We propose a formalization predicting that high contributors will selfselect into groups committed to charitable giving. Testing this experimentally, we let subjects choose between two group types, where one type donate a fixed amount to a charity. Contributions in these groups stayed high, whereas contributions in the other groups showed the well known declining pattern. One implication is that corporate social responsibility may attract more responsible employees.
Keywords: D11; D12; D64; H41; 330; Altruism; conditional cooperation; self-selection; Öffentliches Gut; Spieltheorie; Altruismus; Corporate Social Responsibility; Konsumentenverhalten; Test